Investigation of chemical interactions of small peptides and vitamin substances at the developed dopamine D2 receptor models - Aslancan, R.; Aksoydan, B.; Kantarcioglu, I.; Erol, I.; Salmas, R. E.; Durdagi, S. (Elsevier France-Editions Scientifiques Medicales Elsevier, 2017)
[No abstract available]